2022
DOI: 10.1108/jamr-12-2021-0370
|View full text |Cite
|
Sign up to set email alerts
|

Absorptive capacities, FDI and economic growth in a developing economy: a study in the Indian context

Abstract: PurposeThe purpose of the study is to examine the moderating impact of absorptive capacity on the foreign direct investment (FDI)–growth link using the data for the period 1995–2019.Design/methodology/approachThe authors apply the autoregressive distributed lag (ARDL) model and threshold analysis for empirical analysis.FindingsThe findings indicate that the link between FDI and economic growth is influenced indirectly by absorptive capacities, such as financial development, institutional quality, technological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 74 publications
0
10
0
Order By: Relevance
“…After conducting an extensive literature review, we concluded that data on FDI flows in developing countries with emerging markets play an essential role in transferring technologies through their linkage to energy sector production chains, fostering the construction of renewable energy infrastructure (Mahbub & Jongwanich, 2019;Azam & Haseeb, 2021). Capital flows, in addition to encompassing the definitions of the theoretical lens of this paper, give organizations the ability to exchange capabilities and resources for their financial management in multinationals in the infrastructure sectors (Rocha et al, 2017;Ross, 2019;Azam & Haseeb, 2021;Gupta et al, 2022).…”
Section: Foreign Direct Investment and Organizational Dynamic Capabil...mentioning
confidence: 95%
See 2 more Smart Citations
“…After conducting an extensive literature review, we concluded that data on FDI flows in developing countries with emerging markets play an essential role in transferring technologies through their linkage to energy sector production chains, fostering the construction of renewable energy infrastructure (Mahbub & Jongwanich, 2019;Azam & Haseeb, 2021). Capital flows, in addition to encompassing the definitions of the theoretical lens of this paper, give organizations the ability to exchange capabilities and resources for their financial management in multinationals in the infrastructure sectors (Rocha et al, 2017;Ross, 2019;Azam & Haseeb, 2021;Gupta et al, 2022).…”
Section: Foreign Direct Investment and Organizational Dynamic Capabil...mentioning
confidence: 95%
“…Capital inflows drive infrastructure advancement in developing economies by enabling the direction of investment flows to transportation, energy, sanitation, and health sectors (Ross, 2019;Azam & Haseeb, 2021;Gupta, Yadav, & Jain, 2022).…”
Section: Foreign Direct Investment As a Vector Of Resource Orchestrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Absorptive capacity is defined by Fayad and El Ebrashi (2022) as having two components: previous knowledge and degree of activity. Gupta et al. (2022) also reveal that members’ abilities are gained through work-related talents, as well as their academic foundation and experience, which may signify the depth of background knowledge already accumulated.…”
Section: Literature Review and Hypothesismentioning
confidence: 99%
“…Absorptive capacity is defined by Fayad and El Ebrashi (2022) as having two components: previous knowledge and degree of activity. Gupta et al (2022) also reveal that members' abilities are gained through work-related talents, as well as their academic foundation and experience, which may signify the depth of background knowledge already accumulated. Despite having a significant intellectual ability, a person's capacity for absorption is limited if they lack or lack the will to study, which might affect project performances.…”
Section: Project Performance and Absorptive Capacitymentioning
confidence: 99%